UNC119 is required for G protein trafficking in sensory neurons - Zhang, Houbin (2011)
UNC119 is widely expressed among vertebrates and invertebrates. Here we report that UNC119 recognized the acylated N-terminus of the rod photoreceptor transducin α-subunit (Tα) as well as C. elegans G proteins Odr-3 and Gpa-13. The crystal structure of human UNC119 at 1.95 Å resolution revealed an immunoglobulin-like β-sandwich fold. Pulldowns and isothermal titration calorimetry revealed a tight interaction between UNC119 and acylated Gα peptides. Co-crystallization of UNC119 with an acylated Tα N-terminal peptide at 2.0 Å revealed that the lipid chain is buried deeply into UNC119's hydrophobic cavity. UNC119 bound Tα(GTP) inhibiting its GTPase activity, thereby providing a stable UNC119-Tα(GTP) complex that is capable of diffusing from the inner segment back to the outer segment following light-induced translocation. UNC119 deletion in both mouse and C. elegans lead to G protein mislocalization. These results establish UNC119 as a novel Gα-subunit cofactor that is essential for G-protein trafficking in sensory cilia.